Changing pattern of acquisition behaviour in takeovers and the consequences for acquisition processes - Hunt, John W. (Strategic Management Journal, 1990)
Since 1985 the U.K. and American corporate markets have been seeing, for the fourth time this century, boom conditions in the acquisition and merging of companies. Most predictions suggest this pattern will continue into the 1990s. Yet the failure of acquired companies remains at 50 per cent. In an attempt to understand this failure rate Kitching's seminal work (1967, 1973) is used as a starting point. His hypothesized relationships for success or failure are tested against a recent U.K. study of 40 cases, and found to be insufficient to explain success or failure. A paradigm of contextual and process variables is proposed as a fuller explanation of the phenomenon. Finally, different contexts and different behavioural processes are suggested as more substantial explanations of outcomes.